A unified deterrence-based model of legal and non-legal factors that influence young driver speeding behaviour. (September 2021) - Truelove, Verity; Freeman, James; Kaye, Sherrie-Anne; Watson, Barry; Mills, Laura; Davey, Jeremy
Highlights: Three deterrence-based theories were combined to predict young driver speeding. A high perceived severity of punishment predicted less frequent speeding. Certainty of apprehension was a deterrent via a high perceived punishment severity. Avoiding punishment and perceptions of safety predicted more frequent speeding. Abstract: Young driver speeding behaviour remains a large contributor to road trauma worldwide. In order to provide a more-in depth understanding of how to deter young drivers from this behaviour, this study developed and tested a model of the legal and non-legal factors that influence young driver's intentional speeding behaviour (exceeding the speed limit by more than 10 km/hr). A prospective survey design was conducted to measure the impact of perceptions of legal factors (including classical deterrence and reconceptualised deterrence variables) and non-legal factors (including the variables of fear of physical loss, material loss and perceived social sanctions, as well as the perception that it is safe to engage in the behaviour without being involved in a crash) at time 1, on engagement in speeding behaviour at time 2, which occurred 3 months later. A total of 200 participants aged 17–25 years completed both surveys (Mean age = 20.44 years). Using structural equation modelling, a unique model combining classical and extended deterrence theory, as well as prominent non-legal factors was created, and the variables were able to explain 41% of the variance in speeding behaviour. A high perceived severity of the punishment, experiencing direct punishment avoidance and perceiving that it is safe to speed were significant direct predictors. Meanwhile, there were also numerous significant partially mediated relationships found for both legal and non-legal variables. These findings provide important implications for both the application of deterrence-based theories in road safety and for improving countermeasures to deter young drivers more effectively from engagement in speeding.